2017
DOI: 10.1002/ejoc.201700756
|View full text |Cite
|
Sign up to set email alerts
|

Facile Coupling of Aldehydes with Alcohols: An Evolved Tishchenko Process for the Preparation of Unsymmetrical Esters

Abstract: A facile coupling process between aldehydes and alcohols to afford unsymmetrical esters is presented herein. This transformation is complementary to the Tishchenko reaction and provides access to unsymmetrical esters under very mild conditions. Various aldehydes and alcohols are suitable in this reaction, and the addition of a sacrificial trifluoromethyl ketone allows the process to take place in a highly selective manner. A plausible mechanism based on details obtained by monitoring the reaction progress and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Eisen and co‐workers developed a supportive reaction to Tishchenko reaction to generate unsymmeterical ester compounds (Scheme ) . This complementing Tishchenko reaction produced asymmetrical esters under mild conditions and with high yields.…”
Section: Mechanism and Reactionsmentioning
confidence: 99%
“…Eisen and co‐workers developed a supportive reaction to Tishchenko reaction to generate unsymmeterical ester compounds (Scheme ) . This complementing Tishchenko reaction produced asymmetrical esters under mild conditions and with high yields.…”
Section: Mechanism and Reactionsmentioning
confidence: 99%
“…We have shown that if throughout a catalytic insertion process the system initiates with a metal‐oxygen bond, however, after the catalytic transformation, a different metal‐oxygen bond is obtained, ideally and thermodynamically speaking, the system is thermoneutral as regards to the M–O bond however, the system must be able to reach the necessary energy of activation to be able to catalyze the transformation …”
Section: Introductionmentioning
confidence: 99%
“…Hafnium complexes have mainly been used for the catalytic homo- and copolymerization of α-olefins and as Lewis acid catalysts in various organic transformations including the polymerization of cyclic esters. More recently, Hf–MOF complexes have been utilized in the catalytic activation of small molecules. Among the group-IV metals, hafnium is considered to be the most oxophilic metal when compared with zirconium and titanium, as illustrated by their corresponding metal–oxygen bond dissociation energies (Ti–O = 666 kJ/mol, Zr–O = 766 kJ/mol, and Hf–O = 801 kJ/mol) . Hence, the strong metal–oxygen bond and the high electrophilicity of the metal have precluded the use of organometallic complexes of hafnium in processes involving oxygen-containing moieties with acidic protons. We have postulated that if, during a stoichiometric or a catalytic process, we start with a metal–oxygen bond and after the transformation we end up with a different metal–oxygen bond, then, theoretically, we are not paying thermodynamically for the M–O bond; however, we need to have the energy of activation to be able to execute the process. …”
Section: Introductionmentioning
confidence: 99%